Rancang Bangun Sistem Monitoring Kekeruhan Air Pada Mesin Rotary Drum Filter Berbasis Sensor TSS Dan Mikrokontroler ESP32 - Muhammad Nurul; Dina Maizana (Riau Jurnal Teknik Informatika, 2025)
Industrial wastewater treatment is an important process in maintaining environmental quality. One of the important parameters that must be monitored is the level of water turbidity. This study aims to design and build a real-time water turbidity monitoring system on a rotary drum filter machine using a Total Suspended Solid (TSS) sensor and an IoT-based microcontroller. This system is designed to automatically measure turbidity levels and send data to a web-based monitoring platform. The test results show that the system is able to detect turbidity variations with good accuracy and provide real-time readings. Implementation of this system can improve the efficiency of monitoring and maintenance of rotary drum filter units in wastewater treatment plants. Keywords: Turbidity monitoring, rotary drum filter, TSS sensor, IoT, microcontroller.